Will NICE's quality standard for multiple sclerosis improve care?. Issue 5 (May 2016) - Robinson, Ann
Abstract : In January, NICE published new quality standard statements for the care of people with MS. This article describes the current management of multiple sclerosis in the UK, including the problems and challenges, and discusses whether the new NICE quality standard statements will address them.